Root Canal Irrigation Practice Among General Dental Practitioners in Misurata-Libya: A cross Sectional Study (Journal of Academic Research, 2023)
Objective: The aim of this survey was to evaluate the current trends in the practice of general dental practitioners regarding the root canal irrigation during endodontic treatment in  private and governmental dental clinics in Misurata- Libya.Materials and Methods: A descriptive questionnaire survey was circulated among 220 general dental practitioners  in private and governmental dental clinics in Misurata-Libya. The analysis of data was performed using SPSS.  The descriptive statistics were used for determination of the  frequency and percentage of the participant's responses. Chi-Square test was used to assess the impact of work sector  and  professional  experience on the responses  (P < 0.05). Results: A total of 186 completed the survey questionnaire, giving  a response rate of 84.5%.    Around  99%  of respondents  used sodium hypochlorite in irrigation protocol while EDTA was included by 42%.  60% of respondents  used full strength sodium hypochlorite (5.25%).   83.3% of respondents used smaller  needle gauge (25 and 27).  68% of respondents used syringe capacity ˃5.0 ml.  Only 45% of respondents used irrigation adjuncts and  89%  agitate the irrigation solution  manually.  Around  38% of respondents insert the irrigation needle 2-3 mm from the apex.  The majority of  respondents irrigate the root canals ˂ 10 minutes and do not change their primary irrigation  solution according to the pulpal or periapical status.  No significant impact  observed for  either  the working sector  or professional experience on the responses.Conclusion: General dental  practitioners in Misurata should be encouraged to introduce various techniques and adjuncts to improve the efficacy of endodontic irrigants.